1993
DOI: 10.1246/bcsj.66.57
|View full text |Cite
|
Sign up to set email alerts
|

General Graph Theory of Superaromaticity

Abstract: A conjugated super-ring molecule with a cavity inside may exhibit superaromaticity, i.e., extra thermodynamic stabilization due to the super-ring structure. General graph theory of superaromaticity was developed so as to analyze superaromatic character of all kinds of conjugated super-ring molecules. Typical conjugated super-ring molecules, such as kekulene, azulenoid kekulene, anti-kekulene, octadecabenzokekulene, hexa-m-phenylene, and hexabenz[18]annulene, were predicted to be essentially non-superaromatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
382
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(393 citation statements)
references
References 22 publications
9
382
0
2
Order By: Relevance
“…If a π-system contains three or more rings, one or more terms are necessary in the expansion of P G (X) like eq 19, which represent additional contributions from two or more disjoint circuits. We previously derived the following approximate but amazing formulas to interpret the total π-binding energy E π and TRE for a neutral conjugated hydrocarbon in terms of molecular geometry: 71,72 E % 6:0846 log 10 jP G ðiÞj ð24Þ E % 6:0846 log 10 jR G ðiÞj ð25Þ TRE % 6:0846 log 10 jP G ðiÞj À 6:0846 log 10 jR G ðiÞj ð26Þ where i is the square root of ¹1. The function value «P G (i)« was proposed as a generalized expression for Hosoya's z* index.…”
Section: Visualization Of Aromatic Stabilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…If a π-system contains three or more rings, one or more terms are necessary in the expansion of P G (X) like eq 19, which represent additional contributions from two or more disjoint circuits. We previously derived the following approximate but amazing formulas to interpret the total π-binding energy E π and TRE for a neutral conjugated hydrocarbon in terms of molecular geometry: 71,72 E % 6:0846 log 10 jP G ðiÞj ð24Þ E % 6:0846 log 10 jR G ðiÞj ð25Þ TRE % 6:0846 log 10 jP G ðiÞj À 6:0846 log 10 jR G ðiÞj ð26Þ where i is the square root of ¹1. The function value «P G (i)« was proposed as a generalized expression for Hosoya's z* index.…”
Section: Visualization Of Aromatic Stabilizationmentioning
confidence: 99%
“…4,56 Therefore, we can only say that aromatic species have a greater probability of being kinetically more stable than non-or antiaromatic ones. 57 It, nevertheless, is generally true that highly antiaromatic molecules are too reactive to isolate. As for PAHs, TRE per π-electron is roughly linear in the energy gap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies on the optical characterization of the molten CT complexes have been reported. 831 In the following we describe a drastic decrease in resistivity by a factor of 10 5 -10 6 upon the melting of a neutral alternating CT complex, C 7 TET-TTF Á TCNQ (Chart 15). Syntheses and characterizations of C n TET-TTF have been studied by Otsuka, Saito, et al 832 The molecules with intermediate alkyl chain lengths exhibited considerably low melting points owing to the increased fusion entropy (Fig.…”
Section: Reticulate Doped Polymer (Rdp) Filmsmentioning
confidence: 99%
“…Aihara (17) reported the vapor pressure of benzil as a function of temperature. From his correlation equation…”
Section: Resultsmentioning
confidence: 99%